The art and science of sociology : essays in honor of Edward A. Tiryakian - Robertson, Roland; Simpson, John Herman, 1936-; Tiryakian, Edward A. (Key issues in modern sociology., 2016)
A festschrift honoring the work of Edward A. Tiryakian, consisting of a large number of essays.